2016
DOI: 10.1093/brain/aww228
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased screen identifies aripiprazole as a modulator of abundance of the polyglutamine disease protein, ataxin-3

Abstract: No disease-modifying treatment exists for the fatal neurodegenerative polyglutamine disease known both as Machado-Joseph disease and spinocerebellar ataxia type 3. As a potential route to therapy, we identified small molecules that reduce levels of the mutant disease protein, ATXN3. Screens of a small molecule collection, including 1250 Food and Drug Administration-approved drugs, in a novel cell-based assay, followed by secondary screens in brain slice cultures from transgenic mice expressing the human diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 64 publications
0
43
0
Order By: Relevance
“…Heat shock proteins Hsp40, Hsp70, and Hsp90β, which play important roles in maintaining protein homeostasis in cells 50 , are also altered in SCA3 post-mortem brains and disease model systems [50][51][52][53] . Immunoblot analysis revealed Hsp40 and Hsp70 to be significantly decreased by 50% ± 21% (p = 0.037) and 42% ± 18% (p = 0.039), respectively, in SCA3-hESC relative to WT-hESC (n = 3 passages per line, 2-3 replicates per passage) ( Figure 3G and 3H).…”
Section: Altered Expression Of Key Protein Clearance Pathway Proteinsmentioning
confidence: 99%
“…Heat shock proteins Hsp40, Hsp70, and Hsp90β, which play important roles in maintaining protein homeostasis in cells 50 , are also altered in SCA3 post-mortem brains and disease model systems [50][51][52][53] . Immunoblot analysis revealed Hsp40 and Hsp70 to be significantly decreased by 50% ± 21% (p = 0.037) and 42% ± 18% (p = 0.039), respectively, in SCA3-hESC relative to WT-hESC (n = 3 passages per line, 2-3 replicates per passage) ( Figure 3G and 3H).…”
Section: Altered Expression Of Key Protein Clearance Pathway Proteinsmentioning
confidence: 99%
“…From 1,250 FDA‐approved drugs, it was found that the atypical antipsychotic drug aripiprazole reduces the levels of mutant ATXN3 in both systems. This compound was further tested in vivo in the mouse and fly models of MJD/SCA3 increasing the longevity of the flies and reducing mutant ATXN3 species in the brain of the transgenic mouse model …”
Section: Therapeutic Strategies For Polyq Diseasesmentioning
confidence: 99%
“…To identify genes that regulate levels of pathogenic ATXN3 in mammalian cells, we used our previously developed ATXN3-Luc cellular assay (Figure 1A,B) [13] to screen the druggable genome subset of the human siGENOME siRNA library (Dharmacon). This library comprises SMARTpools of four individual siRNAs targeting 2742 genes that are considered potential therapeutic targets, including G-protein coupled receptors (GPCRs), ion channels, protein kinases, proteases, phosphatases and ubiquitin conjugation enzymes (https://dharmacon.horizondiscovery.com/rnai/).…”
Section: Resultsmentioning
confidence: 99%
“…This library comprises SMARTpools of four individual siRNAs targeting 2742 genes that are considered potential therapeutic targets, including G-protein coupled receptors (GPCRs), ion channels, protein kinases, proteases, phosphatases and ubiquitin conjugation enzymes (https://dharmacon.horizondiscovery.com/rnai/). The ATXN3-Luc assay measures chemiluminescence in HEK293 cells stably overexpressing FLAG-tagged human ATXN3 harboring an expanded polyQ repeat in the disease range (Q81) fused to firefly Luciferase, under the control of a CMV promoter (Figure 1A,B) [13]. We reasoned that by screening for steady state levels of the ATXN3/Luciferase fusion protein (reported as chemiluminescence), and because its expression is driven by the CMV promoter, we would identify genes that regulate ATXN3 abundance at post-transcriptional steps (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation